Parental experiences on the inclusion of their child with down syndrome in a mainstream school - Van den Eijnde, Liezel; De Villiers, Liezel (Stellenbosch : Stellenbosch University, 2021)
ENGLISH SUMMARY : Down syndrome, also known as Trisomy 21, is a genetic disorder that arises because of an additional chromosome due to abnormal cell division during fertilization (Sherman, Allen, Bean, & Freeman, 2007). Research has indicated that the prevalence of Down Syndrome in South Africa, is 1 in every 500 babies, and that Down Syndrome is the leading cause of intellectual impairment in children (Engelbrecht, Swart, & Eloff, 2001). Since the 1980’s, research has established that children with Down syndrome who attend a mainstream school fair better academically and socially than their peers who attend special needs schools (Buckley, Bird, Sacks, & Archer, 2006; Engelbrecht, Swart, & Eloff, 2001; Hughes, 2006). However, limited research has been done towards understanding parents motivations for seeking inclusive learning environments for their child with Down syndrome, as well as their experiences of having their child mainstreamed. The purpose of this study was to gain a deeper understanding of parents’ experiences on the inclusion of their child with Down syndrome in a mainstream school. The study was conducted within an interpretive paradigm and followed a basic qualitative research design. Semi-structured interviews, field notes and reflective essay questions were used to collect data. The data was analysed through thematic content analysis to identify emerging themes from the data. The findings of the study suggests that parents overall experience has been positive, however the cost of mainstreaming is expensive. Thus many parents of children with Down syndrome would not be able to mainstream their children within South Africa recommendations are made based on these findings.